(untitled) (Mongolian Journal of Agricultural Sciences, 2020)
Hydrid lams of Dorper x Native sheep weighted with 44.5-61.1 kg live were selected and divided into three experimental groups. Each experimental groups were fed by 50 percentages grass, 50 percentages of cereals and 50 percentages of mineral containing fees separately. Methane gas emission was measured from animal fed by pellets amounted 2.5 kg, 1.48 kg and 1.11 kg for first, second and third groups, respectively. During the study period, sheep extricated 6.65 liters, 5.05 liters and 1.78 liters of methane gas. The methane extraction was 24.1-71.8 percentage higher in first feeding groups compared to other two groups (P<0.01). The very strong positive correlation was found between he feed intake and methane gas emission. In other words, 67.0 percentages of methane gas emission were caused by the feed intake. Метан хийн ялгаралт тэжээлийн идэмжээс хамаарах нь Бид судалгаанд “Нутгийн х Дорпер” хонины F1 эрлийз, 44.5-61.1 кг амьдын жинтэй 15 хонийг сонгож туршилтын 3 бүлэгт (n=5) хувааж бүдүүн тэжээл 50, хүчит, эрдэс тэжээл 50 хувь бүхий жороор тэжээв. Туршлагын бүлгүүдэд хорголжин тэжээлийг хоногт I-р бүлэгт 2.5 кг, II-р бүлэгт 1.48 кг, III-р бүлэгт 1.11 кг-аар өгч метан болон нүүрсхүчлийн хийн ялгаралтыг судлав. Туршилтын хугацаанд I-р бүлгийн хонь 6.65 л, II-р бүлгийнх 5.05 л, III-р бүлгийнх 1.78 л метан хий ялгаруулсан ба I бүлэг бусад бүлгийнхээс 24.1-71.8 хувиар илүү ялгаруулсан байна (P<0.01). Метан хийн ялгаралт, тэжээлийн идэмж хоорондын хамаарлыг судлахад эерэг хамааралтай буюу 67.0 хувь нь идсэн тэжээлээс хамаарч байна. Түлхүүр үг: идэмж, метан хий, нүүрсхүчлийн хий